Proving that the total mechanical energy is conserved with time

In summary, the total mechanical energy of a system, represented by ##E(t)##, is constant with time. This is proven by taking the derivative of ##E(t)## and setting it equal to 0, which leads to the conclusion that ##-f(x(t)) = ma(t)## and the function ##f(x(t))##, which is equal to ##-V'(x(t))##, represents the force acting on the object in the system. This can also be proven using the work-energy theorem, which states that the change in kinetic energy (KE) and potential energy (PE) will always be equal, resulting in a net change of 0.
  • #1
Hamiltonian
296
193
Homework Statement
Prove that Total mechanical Energy is conserved with time.
Relevant Equations
-
proof of energy being conserved with t.png

To prove: total mechanical energy is constant with time
where ##E(t)## is the total mechanical energy and ##V(x(t))## is the potential energy of the object-system.
$$E(t) = 1/2 mv^2 + V(x(t))$$

taking the the derivative of ##E(t)## with respect time should give 0.
in the third step in the attached file i don't understand why ##-f(x(t)) = ma(t)##
also what is the significance of the function ##f(x(t))## which is equal to ##-V'(x(t))##

my attempt to a solution:
taking an example of a spring and block system(even though its not very general but I thought I'd get the idea).
so i defined ##E = 1/2mv^2 + 1/2kx^2##
from this i got ##E' = v(ma + kx)##
I could not further simplify this.

also I think I was able to prove the above using the work energy theorem ##\Delta KE = -\Delta PE ## hence ##\Delta(KE + PE) = 0##
so what am missing and doing wrong in the above method stated by me.:oldconfused:
 
Physics news on Phys.org
  • #2
It's called Newton's law, usually written as ##F = ma##

In your example ## F = - kx## for a spring.
 
  • Like
Likes Steve4Physics
  • #3
If you like, you can re-state their proof from a slightly different starting point; assuming the particle moves in some potential ##V(x)##, then$$m\ddot{x} = F_x = -V'(x)$$ $$m\ddot{x}\dot{x} = - V'(x) \dot{x}$$ $$\frac{d}{dt} \left(\frac{1}{2}m\dot{x}^2 \right) = -\frac{d}{dt} V(x)$$ $$\frac{d}{dt} \left( \frac{1}{2}m\dot{x}^2 + V(x) \right) = 0 \implies \frac{1}{2}m\dot{x}^2 + V(x) = E = \text{constant}$$
 
  • Like
Likes BvU, PeroK and Hamiltonian
Back
Top